Answer:
5x - 10
Step-by-step explanation:
→ Find the sum of the expression
3x - 4 + 2x - 6
→ Collect all the x terms
3x + 2x - 4 - 6
→ Simplify
5x - 10
Answer:
1: 8a²
2: 9a²b²c²
Step-by-step explanation:
1: 48a³ ÷ 6a
48÷6 = 8
8a²
2: 72a³b⁴c⁵ ÷ 8ab²c³
72÷ 8 =9
9a²b²c²
Answer:
Step-by-step explanation:
Triangle GEF is a right angle triangle.
From the given right angle triangle
GE represents the hypotenuse of the right angle triangle.
With ∠E as the reference angle,
FE represents the adjacent side of the right angle triangle.
FG represents the opposite side of the right angle triangle.
To determine tan E, we would apply the tangent trigonometric ratio
Tan θ = opposite side/adjacent side. Therefore,
Tan E = 56/33
Tan E = 1.69697
It becomes 1.70 to the nearest hundredth.
Answer:
CED=126
Step-by-step explanation:
The total of all 3 angles should be 180
so:
180-38-16 (ABC is equal to ECD)
180-38-16=126
126=CED
Answer:
2
Step-by-step explanation:
Let f(x) = 2x – 1
Substitute (x + b) in place of x.
f(x + b) = 2(x + b) – 1
= 2x + 2x –1
To find
:
![\frac{f(x+b)-f(x)}{(x+b)-x}=\frac{(2x+2b-1)-(2x-1)}{(x+b)-x}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%2Bb%29-f%28x%29%7D%7B%28x%2Bb%29-x%7D%3D%5Cfrac%7B%282x%2B2b-1%29-%282x-1%29%7D%7B%28x%2Bb%29-x%7D)
![=\frac{2x+2b-1-2x+1}{x+b-x}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x%2B2b-1-2x%2B1%7D%7Bx%2Bb-x%7D)
(Cancel common term)
![=2](https://tex.z-dn.net/?f=%3D2)
Hence, ![\frac{f(x+b)-f(x)}{(x+b)-x}=2.](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28x%2Bb%29-f%28x%29%7D%7B%28x%2Bb%29-x%7D%3D2.)